Morphological dependent exciton dynamics and thermal transport in MoSe2 films - Gupta J.D.; Jangra P.; Majee B.P.; Mishra A.K. (My University, 2025)
Thermal transport and exciton dynamics of semiconducting transition metal dichalcogenides (TMDCs) play an immense role in next-generation electronic, photonic, and thermoelectric devices. In this work, we synthesize distinct morphologies (snow-like and hexagonal) of a trilayer MoSe2 film over the SiO2/Si substrate via the chemical vapor deposition (CVD) method and investigated their morphological dependent exciton dynamics and thermal transport behaviour for the first time to the best of our knowledge. Firstly, we studied the role of spin-orbit and interlayer couplings both theoretically as well as experimentally via first-principles density functional theory and photoluminescence study, respectively. Further, we demonstrate morphological dependent thermal sensitive exciton response at low temperatures (93-300 K), showing more dominant defect-bound excitons (EL) in snow-like MoSe2 compared to hexagonal morphology. We also examined the morphological-dependent phonon confinement and thermal transport behaviour using the optothermal Raman spectroscopy technique. To provide insights into the nonlinear temperature-dependent phonon anharmonicity, a semi-quantitative model comprising volume and temperature effects was used, divulging the dominance of three-phonon (four-phonon) scattering processes for thermal transport in hexagonal (snow-like) MoSe2. The morphological impact on thermal conductivity (ks) of MoSe2 has also been examined here by performing the optothermal Raman spectroscopy, showing ks ∼ 36 ± 6 W m−1 K−1 for snow-like and ∼41 ± 7 W m−1 K−1 for hexagonal MoSe2. Our research will contribute to the understanding of thermal transport behaviour in different morphologies of semiconducting MoSe2, finding suitability for next-generation optoelectronic devices. © 2023 The Author(s).